The Prognostic Value of Total Blood Count Parameter Ratios in Acute Pulmonary Embolism - Aynur Yurtseven; Kerem Ensarioğlu (Diagnostics)
Background/Objectives: Acute pulmonary embolism (PE) is a leading cause of cardiovascular mortality, characterized by nonspecific symptoms and variable clinical presentations. Accurate risk stratification is essential for effective management. While conventional tools like the simplified pulmonary embolism severity index (sPESI) and imaging modalities are widely used, they are often costly and have limitations in predictive accuracy. Inflammatory and coagulative markers, such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean-platelet-volume-to-lymphocyte ratio (MPVLR), have shown promise in thrombotic conditions. This study explores their prognostic value in PE, focusing on their associations with risk stratification and clinical outcomes. Methods: This retrospective study included 231 adult patients diagnosed with PE at a tertiary care center. Exclusion criteria included recent infection, autoimmune diseases, or immunosuppressive therapy. Laboratory data, clinical parameters, and outcomes (e.g., hospitalization duration, complications, and mortality) were analyzed. Ratios were calculated from routine blood counts, and statistical comparisons were conducted between low- and high-risk groups based on sPESI. Results: High-risk patients (n = 203) exhibited significantly higher troponin, blood urea nitrogen, aspartate aminotransferase, lactate, the NLR (median 4.9 vs. 2.7, p = 0.005), and the MPVLR (median 7.1 vs. 3.9, p = 0.001) compared to low-risk patients. The PLR showed no significant difference between risk groups (p = 0.233). An elevated NLR, PLR, and MPVLR correlated with ICU admission, intubation, and mortality (p < 0.001, p < 0.007, and p < 0.001, respectively). The NLR was the most consistently associated with hospitalization duration and mortality, while the MPVLR and PLR were less predictive of overall hospitalization. Conclusions: The NLR, MPVLR, and PLR are cost-effective, easily calculable markers with the potential for improving risk stratification in PE patients. Among these, the NLR showed the strongest prognostic value, correlating with multiple clinical outcomes. Multicenter studies are needed to validate these findings further and establish clinical utility.